Analisis Profitabilitas Pada Bank Syariah Indonesia Pada Tahun (2021-2022) - Irma Listiani; Muhammad Reza Ardhana; Chairina Chairina (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to determine the profitability of Islamic banks in Indonesia. Banking as a player in a field that requires financial trust from its customers. Return On Assets (ROA) Measuring a company's ability to generate profits, which can be considered by investors in investing. All Islamic banks in Indonesia will take part in this survey from 2022 to 2021. The results show that the Tertiary Finance (DPK) and Operational Performance (BOPO) variables have a positive and insignificant effect. Unorganized Finance (NPF) and Financial Deposit Ratio (FDR) variables have a negative and significant effect.